A RP-HPLC Method for the Analysis of Neostigmine Methylsulfate and Process-Related Impurities, Forced Degradation Studies, in the Injection Formulation - Manali Parab; Vaishali A. Shirsat; Yogita M. Kodgule; Mandar Kodgule (International Journal of Analytical Chemistry)
Neostigmine methylsulfate is an anticholinesterase agent and is clinically used for treating myasthenia gravis. It is also used for reversing nondepolarising neuromuscular blocking agents. Neostigmine methylsulfate may be administered by intravenous, intramuscular, or subcutaneous injection. In this research paper, a distinct stability-indicating reverse phase HPLC method was developed and validated for the quantitative determination of related impurities and degradation impurities in neostigmine methylsulfate API and injection formulation. The specific objective was to improve the resolution between European Pharmacopoeia listed impurity A and impurity B and degradation impurity of neostigmine methylsulfate API and injection formulation. The analysis was performed using Kromasil C18 column at 30°C of column oven temperature with phosphate-buffer/acetonitrile in a gradient mode. The RP-HPLC method was developed and validated for in-house neostigmine methylsulfate synthesis process sample and injection formulation. The injection formulation sample was studied for accelerated stability, temperature cycling stability, and photostability. The validation studies for neostigmine methylsulfate synthesis process API were studied using impurity A, impurity B, and impurity C. The analytical method validation parameters studied were specificity, precision, linearity, limit of detection, limit of quantitation, accuracy, and robustness. The API and the injection formulation were subjected to forced degradation under acid, alkali, oxidation, and photolytic and thermal conditions. The proposed method showed a significantly improved RRT (Relative Retention Time) of impurity A and impurity B with a resolution greater than 1.5. The developed method eliminates the use of an ion-pairing agent and thereby a good performance of column was established.